Management of Childhood Urticaria: Current Knowledge and Practical Recommendations - Pite, H (2013)
Urticaria, defined by the presence of wheals and/or angioedema,is a common condition in children, prompting parents to consult physicians. For its successful management, paediatric-specific features must be taken into account, regarding the identification of eliciting triggers and pharmacological therapy. This review systematically discusses the current best-available evidence on spontaneous acute and chronic urticaria as well as physical and other urticaria types in children. Potential underlying causes, namely infections, food and drug hypersensitivity, autoreactivity and autoimmune or other conditions, and eliciting stimuli are considered, with practical recommendations for specific diagnostic approaches. Second-generation antihistamines are the mainstay of pharmacological treatment aimed at relief of symptoms, which require dose adjustment for paediatric use. Other therapeutic interventions are also discussed. In addition, unmet needs are highlighted, aiming to promote research into the paediatric population, ultimately aiming at the effective management of childhood urticaria.